多環梯形有機共軛分子於有機太陽能電池之應用 - 鄭彥如; Cheng Yen-Ju (My University, 2014)
要達到高效率之有機太陽能電池，在分子層面上最大的挑戰為發展溶液製程之有機材料 同時要能夠擁有低的光學能隙以提升光吸收的能力，以及高的電洞傳輸率已增加光電 流。利用化學共價鍵的方法把相鄰的芳香環固定連結起來，可以幫助電子的非定域化， 延長有效共軛長度，進而降低能階。藉以固定芳香環之間的平面化，抑制分子間的轉動， 如此可增強分子間之作用力、誘導分子結晶性來增加電荷傳輸速率。本計畫我們將設計 合成一系列新穎之梯型結構包括四、五、六、七、十環互為熔合之共軛系統，以實現高 效率之有機太陽能電池。這類共軛系統將由苯環、噻吩、吡咯、咔唑、芴、噻咯以及 環戊二烯之基礎單元所組成。並且引入雙邊硼酯或雙邊錫烷基與雙邊溴化之缺電子單體 進行聚合反應，可形成一系列之施體與受體所交錯之D-A 共軛高分子。同時也將與單邊 溴化之缺電子單體，進行雙邊的偶合反應，形成結構明確，分子量單一，高純度之A-D-A 的小分子。利用這些芳香環或雜環的立體特性與分子軌域的不同，將提供很好的方式來 調控這些半導體材料的光物理與電學性質。最後以這些新型有機材料製備有機太陽能電 池來達到最佳化之效率。

To achieve high efficiency of organic photovoltaics, the most critical challenge at molecular level is to develop solution processable organic materials that possess low band-gap (LBG) to capture more solar photons, and high hole mobility for efficient charge transport. Forced planarization by covalently fastening adjacent aromatic units in polymeric backbone can facilitate π-electron delocalization and elongate effective conjugation length, thus effectively reducing the optical band-gap. Furthermore, chemical rigidification restricts the rotational disorder around interannular single bonds to reduce the reorganization energy, thus enhancing intrinsic charge mobility. In this proposal, we will design and synthesize a series of novel ladder-type tetracyclic, pentacylic, hexacyclic, hepatacyclic and decacylic arenes in order to achieve high performance organic photovoltaics. Benzene, thiophene, carbazole, fluorene, pyrrole, silole, cyclopentadienyl units are molecular ingredients to construct these multifused conjugated systems. These arenes, functionalized with boronic ester or trimethylstannyl groups at two ends, will be copolymerized with various di-brominated acceptor units to afford a range of new donor-acceptor alternating copolymers. Meanwhile, these ladder-type arenes will also be reacted with mono-brominated monomers to afford A-D-A small molecules with well-defined chemical structures. The aromatic and heteroaromatic units with different steric and orbital nature will provide a useful way to tailor the optical and electronic properties of these semiconductor materials. Solution processed bulk-heterojunction solar cells will be fabricated to evaluate these newly developed conjugated polymers and small molecules.
Multifused Ladder-Type Conjugated Molecules for Organic Photovoltaics